Cholesterol in the ciliary membrane as a therapeutic target against cancer - Kimura, Sotai; Morita, Tomoka; Hosoba, Kosuke; Itoh, Hiroshi; Yamamoto, Takashi; Miyamoto, Tatsuo (Frontiers in Molecular Biosciences, 2023)
Primary cilium is a non-motile, antenna-like structure that develops in the quiescent G0 phase-cell surface. It is composed of an array of axonemal microtubules polymerized from the centrosome/basal body. The plasma membrane surrounding the primary cilium, which is called the ciliary membrane, contains a variety of receptors and ion channels, through which the cell receives extracellular chemical and physical stimuli to initiate signal transduction. In general, primary cilia disappear when cells receive the proliferative signals to re-enter the cell cycle. Primary cilia thus cannot be identified in many malignant and proliferative tumors. In contrast, some cancers, including basal cell carcinoma, medulloblastoma, gastrointestinal stromal tumor, and other malignancies, retain their primary cilia. Importantly, it has been reported that the primary cilia-mediated oncogenic signals of Hedgehog, Wnt, and Aurora kinase A are involved in the tumorigenesis and tumor progression of basal cell carcinoma and some types of medulloblastoma. It has also been demonstrated that cholesterol is significantly more enriched in the ciliary membrane than in the rest of the plasma membrane to ensure Sonic hedgehog signaling. A series of epidemiological studies on statin drugs (cholesterol-lowering medication) demonstrated that they prevent recurrence in a wide range of cancers. Taken together, ciliary cholesterol could be a potential therapeutic target in primary cilia-dependent progressive cancers.